2015
DOI: 10.1063/1.4919808
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal conductivity enhancement of aqueous suspensions containing silver nanoparticles

Abstract: A thermal conductivity model of nanofluids based on particle size distribution analysis Appl. Phys. Lett. 105, 083117 (2014); 10.1063/1.4894254 Shear-rate dependent effective thermal conductivity of H2O+SiO2 nanofluids Phys. Fluids 25, 052002 (2013); 10.1063/1.4802049 Thermal conductivity of polyethylene glycol nanofluids containing carbon coated metal nanoparticles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…8c. The silver nanoparticles exhibit tremendous thermal conductivity when added with the base fluids [14]. Further, nanoparticles decline the abrasion among the two contact surfaces due to rolling action of nanoparticles, resulting in decrease in wear at the inserts [4]; hence, a smooth surface with a small spiny teeth is identified as shown in Fig.…”
Section: Chip Morphologymentioning
confidence: 99%
“…8c. The silver nanoparticles exhibit tremendous thermal conductivity when added with the base fluids [14]. Further, nanoparticles decline the abrasion among the two contact surfaces due to rolling action of nanoparticles, resulting in decrease in wear at the inserts [4]; hence, a smooth surface with a small spiny teeth is identified as shown in Fig.…”
Section: Chip Morphologymentioning
confidence: 99%
“…Godson et al [13,14] in their work found an increment in thermal conductivity of 80% with 0.9 vol% and 115% for 1.2 vol% of Ag nanoparticles in water. Iyahraja and Rajadurai [15], in the study on polyvinylpyrrolidone coated on silver nanoparticles dispersed in distilled water found an enhancement in thermal conductivity of 69 % with a low volume percentage of 0.1%. As proven by other researchers, Bashirnezhad et al [16] in their review article reported that the viscosity enhances with nanoparticle concentration and decreases with increase in the temperature.…”
Section: Introductionmentioning
confidence: 96%
“…For example, Chen et al [22] employed a seed mediated method to synthesize Au nanoparticles with different diameters and the results demonstrated that an enhanced light absorption at a low mass fraction of Au nanoparticles relative to working fluid was ascribed to LSPR. Compared to Au, Ag displayed a more attractive appeal in solar thermal energy owing to its lower price with comparable photo-thermal conversion performance [23][24][25][26]. As reported by Chen et al [27], Ag nanoparticles were fabricated by an effective seeded growth strategy with limited spaces, which promoted absorption of sunlight from the near-infrared region to the visible region.…”
Section: Introductionmentioning
confidence: 99%